AAV-mediated transcription factor EB (TFEB) gene delivery ameliorates muscle pathology and function in the murine model of Pompe Disease - Francesca Gatto (Nature Portfolio, 2017)
Abstract Pompe disease (PD) is a metabolic myopathy due to acid alpha-glucosidase deficiency and characterized by extensive glycogen storage and impaired autophagy. We previously showed that modulation of autophagy and lysosomal exocytosis by overexpression of the transcription factor EB (TFEB) gene was effective in improving muscle pathology in PD mice injected intramuscularly with an AAV-TFEB vector. Here we have evaluated the effects of TFEB systemic delivery on muscle pathology and on functional performance, a primary measure of efficacy in a disorder like PD. We treated 1-month-old PD mice with an AAV2.9-MCK-TFEB vector. An animal cohort was analyzed at 3 months for muscle and heart pathology. A second cohort was followed at different timepoints for functional analysis. In muscles from TFEB-treated mice we observed reduced PAS staining and improved ultrastructure, with reduced number and increased translucency of lysosomes, while total glycogen content remained unchanged. We also observed statistically significant improvements in rotarod performance in treated animals compared to AAV2.9-MCK-eGFP-treated mice at 5 and 8 months. Cardiac echography showed significant reduction in left-ventricular diameters. These results show that TFEB overexpression and modulation of autophagy result in improvements of muscle pathology and of functional performance in the PD murine model, with delayed disease progression.